Performativitas Komunitas Virtual: Suatu Analisis dari Teori Jaringan-Aktor dalam Komunitas Virtual NFT - Idhar Resmadi; Rendy Pandita Bastari; Lingga Agung; Luqman Rusdan Nugraha (Fakultas Seni Rupa dan Desain ITB, 2022)
Visual artists used NFT (non-fungible tokens) to market artwork and build virtualcommunity networks. NFTs are special certificates or licenses for digitally sold items.In this context, the presence of NFT creators has given rise to a virtual communityinvolving many digital media activities. The phenomenon then offers a variety of newtechnology-based relationships (blockchain, metaverse, NFT, Twitter, Twitter Spaces,Discord, and Clubhouse) and human actors (artists, digital artists, and designers), whichgive rise to specific characteristics to interact with each other or market their artworkin a virtual community. This research aims to discuss the interaction process in the NFT virtual community to understand the NFT ecosystem based on digital media. The actor- network theory is used to understand the network relations between human and non-human actors interacting through various digital platforms. The results of this study showed that the NFT virtual community could not be separated from the presence ofhuman and non-human actors.